2014
DOI: 10.1371/journal.pone.0108986
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Admission Serum Creatinine Concentration with Age and Gender on the Prognostic Significance of Subjects with Acute ST-Elevation Myocardial Infarction in China

Abstract: Objectiveto explore the impact of admission serum creatinine concentration on the in-hospital mortality and its interaction with age and gender in patients with acute ST-segment elevation myocardial infarction (STEMI) in China.Methods1424 acute STEMI patients were enrolled in the study. Anthropometric and laboratory measurements were collected from every patient. A Cox proportional hazards regression model was used to determine the relationships between the admission serum creatinine level (Cr level), age, sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Cardiac failure is a common severe complication of AMI and also one of the major causes of patients with AMI. 12 Peacock et al found that, 13 acute coronary syndrome induced severe myocardial ischemia was the direct cause of acute decompensated heart failure of 14% of patients with chronic cardiac failure and elders were more likely to develop acute coronary syndrome induced acute decompensated heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac failure is a common severe complication of AMI and also one of the major causes of patients with AMI. 12 Peacock et al found that, 13 acute coronary syndrome induced severe myocardial ischemia was the direct cause of acute decompensated heart failure of 14% of patients with chronic cardiac failure and elders were more likely to develop acute coronary syndrome induced acute decompensated heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of serum cholesterol and creatinine were important risk factors for early mortality in elderly patients [ 13 ]. Chen et al also found serum Cr concentration on admission was a strong predictor for in-hospital mortality among Chinese acute STEMI patients especially in the young and the female [ 14 ]. Gevaert et al examined gender differences in the prevalence and prognostic performance of renal dysfunction at admission in this setting.…”
Section: Discussionmentioning
confidence: 99%